Development, Evaluation, and in vitro Anti-Acne Activity of Tretinoin Nanocrystals Gel - Shinu, Pottathil; Sharma, Akash; Nair, Anroop B.; Kumar, Manish; Khan, Shahzad; Al Mouslem, Abdulaziz K.; Morsy, Mohamed A.; Tiwari, Abhishek; Tiwari, Varsha; Kumari, Beena (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Tretinoin is generally used to treat acne vulgaris and photoaging. The study aimed to develop a gel composition containing tretinoin nanocrystals and characterize and compare in vitro anti-acne activity. Materials and Methods: The anti-solvent precipitation approach was used to prepare tretinoin nanocrystals. The drug nanocrystals were optimized for parameters such as particle size, drug content, and drug release. The optimized nanocrystals (TN9) were incorporated into the gel system (TNG1-TNG5) and characterized for pharmaceutical properties. The selected formulation (TNG1) was tested for anti-acne activity using Propionibacterium acnes and Staphylococcus epidermidis and compared with Doxycycline HCl as standard. Results: Nanocrystals (TN9) showed the lowest particle size of 114.2 nm, the least value of polydispersity of 0.232, the highest drug content of 95.24%, and higher cumulative drug release of 97.2% in 10 hr. TEM and DSC images conformed to the nano-size range and crystalline nature of nanocrystals. The prepared gel composition indicates a clear, smooth, and homogeneous nature, good spreadability, suitable viscosity, pH, and drug content. The drug release from TNG1 was found to be significant (p < 0.0001) and was superior to the commercial gel. Results of anti-acne activity signify that the zone of inhibition exhibited by tretinoin nanocrystals was comparable with Doxycycline HCl (standard) for both microorganisms tested. Conclusion: These results demonstrated that the developed tretinoin nanocrystals could be a feasible approach for effective therapy in the treatment of acne.
Keywords: Tretinoin; Nanocrystals; Gel; Drug release; Anti-acne activity; Propionibacterium acnes; Staphylococcus epidermidis